Learn Cocoa on the Mac - Nutting, Jack.; Mark, David; LaMarche, Jeff.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The Cocoa frameworks are some of the most powerful frameworks for creating native desktop applications available on any platform today, and Apple gives them away, along with the Xcode development environment, for free! However, for a first-time Mac developer, just firing up Xcode and starting to browse the documentation can be a daunting task. The Objective-C class reference documentation alone would fill thousands of printed pages, not to mention all the other tutorials and guides included with Xcode. Where do you start? Which classes are you going to need to use? How do you use Xcode and the rest of the tools? This book answers these questions and more, helping you find your way through the jungle of classes, tools, and new concepts so that you can get started on the next great Mac OS X application today. Jack Nutting is your guide through this forest; he's lived here for years, and he'll show you which boulder to push, which vine to chop, and which stream to float across in order to make it through. You will learn not only how to use the components of this rich framework, but also which of them fit together, and why. Jack Nutting$1 (Bs approach, combining pragmatic problem-solving with a deep respect for the underlying design philosophies contained within Cocoa, stems from years of experience using these frameworks. He$1 (Bll show you which parts of your application require you to jump in and code a solution, and which parts are best served by letting Cocoa take you where it wants you to go. The path over what looks like a mountain of components and APIs has never been more thoroughly prepared for your travels. With Jack$1 (Bs guidance, the steep learning curve becomes a pleasurable adventure. There is still much work for the uninitiated, but by the time you$1 (Bre done, you will be well on your way to becoming a Cocoa master.s
Must Love Cocoa -- Hello, World -- Lights, Camera... Actions! (and Outlets, Too) -- GUI Components -- Using Table Views -- Cocoa Bindings -- Core Data Basics -- Core Data Relationships -- Search and Retrieve Core Data with Criteria -- Windows and Menus and Sheets -- Document-Based Applications -- Exceptions, Signals, Errors, and Debugging -- Drawing in Cocoa -- Advanced Drawing Topics -- Working with Files -- Concurrency -- Future Paths.
Keywords: Computer science; Data structures (Computer science).; Computer Science; Data Structures, Cryptology and Information Theory